The natal plumages of antpittas (Grallariidae): Los plumajes natales de los tororois (Grallariidae) (Ornitología Colombiana, 2021)
In a recent paper, Collins (2010) reviewed the current state of knowledge on passerine natal plumages and discussed their significance and usefulness in phylogenetic reconstructions. Included in this paper was an assessment of the natal plumages of antpittas (Grallariidae). With this brief note I clarify and expand upon Collins's assessment and conclusively demonstrate that Grallaricula antpittas hatch with no natal down and that Grallaria antpittas hatch with a sparse covering of long down plumes.